Evaluasi Implementasi Program Jaminan Kesehatan Nasional terhadap Pasien Stroke di RSUP Dr. Sardjito - Muhammad Dahlan; Ismail Setyopranoto; Laksono Trisnantoro (Jurnal Kebijakan Kesehatan Indonesia, 2017)
ABSTRACTBackground: Since 2014, Indonesia has implemented universal health coverage. In Indonesia, it was named as Jaminan Kesehatan Nasional or JKN. “Quality control and cost control” is the tagline of these program. Health provider such as doctors, nurses and the others health provider must control the quality and the cost of the patient’s treatment. Stroke, as one of the disease which needed such a complex treatment, must be treated as effective as possible.Aim: The aim of this study is evaluating the implementation of the JKN in stroke care especially in Central hospital. Measuring the quality of the care in stroke unit is compulsory in implementation research. Knowing acceptability and fidelity of the rules from JKN by the doctors must be described.Method: This study is mixed method with sequential explanatory design. The qualitative research was a cross sectional research which began in June 15th-July 31st. Interview from three doctors in stroke unit Sardjito General Hospital were performed to know the acceptability of the program.Result: The quality of care in Unit Stroke RSUP Dr. Sardjito from the doctors are good. Rationalization of the drugs and safety of the patients were prioritized. From that conditions the unit got a debt condition. The financial performance from one patient could get debt up to eleven million rupiahs. From the qualitative research, the acceptability of the national formulation slightly didn’t accept by the doctors. Neuro protector and another kind of drugs isn’t on the list. rtPA which can be found in the list is too expensive. Reimbursement from the BPJS was too low. Homecare as one the rehabilitation isn’t covered by BPJS. Back referral system to general practitioner isn’t accepted by the neurologist because of the lack of the facility in puskesmas or PPK I. Research and education in academic hospital didn’t do well because of the lack of patients.Conclusion: National formularies are needed to revised based on the patients need. Reimbursement from BPJS should be higher than before. Homecare patients should be guaranteed by BPJS. Keywords: Universal health coverage, stroke, quality care, implementation research ABSTRAKLatar Belakang: Era baru program asuransi kesehatan nasional mulai 1 Januari 2014 yang diselenggarakan oleh BPJS Kesehatan yang mempunyai target bahwa seluruh masyarakat telah menjadi peserta BPJS pada tahun 2019. Apresiasi diberikan kepada pemerintah atas usahanya melaksanakan JKN. Dalam pelaksanaannya, evaluasi perlu dilakukan terhadap program ini. Stroke sebagai salah satu penyakit mematikan dan perlu manajemen yang menyeluruh patut untuk dievaluasi. Penerimaan penyedia pelayanan kesehatan dalam hal ini dokter perlu diidentifikasi.Tujuan: 1) Mengukur kinerja pelayanan; 2) Mengukur kinerja keuangan; 3) mengetahui penerimaan dan ketaatan pemberi pelayanan terhadap aturanMetode: mixed method dengan desain sekuensial ekplanasi. Penelitian kualitatif merupakan cross sectional dimulai 15 Juni–31 Juli. Interview dengan tiga dokter di Unit Stroke Rumah Sakit Umum Pusat Sardjito dilakukan untuk menggambarkan penerimaan.Hasil: Mutu pelayanan penyakit stroke sudah sesuai dengan mutu standar. Rasionalisasi obat, maupun pemulangan pasien tetap sesuai standar. Performa keuangan dari Unit Stroke mengalami kerugian. Penerimaan dari para dokteer terkait beberapa aturan seperti sistem rujukan dan standar tarif belum diterima sepenuhnyaKesimpulan: Permasalahan program Jaminan Kesehatan Nasional masih terjadi. Perbedaan persepsi antara pembuat aturan dengan pemberi pelayanan masih menonjol. Performa keuangan dari unit stroke mengalami kerugian walaupun mutu pelayanan sudah dilakukan secara optimal. Sistem rujukan terutama rujuk balik belum dapat dirasa layak oleh para dokter karena keterbatasan di PPK I. Pelayanan home care yang biasa digunakan tidak dapat optimal karena peserta asuransi belum mendapatkan jaminan untuk memperoleh pelayanan home care. Kata Kunci: jaminan kesehatan nasional, stroke, quality care, implementation research